Icons - Salamé, Louma; Loyrette, Henri 1952-; Biasino, Fabrice; Gorbunova-Lomax, Irina; Rosenoer, Clio (Fondation Boghossian, 2021)
From early icons from Europe and the Middle East to modern and contemporary works, icons have inspired many believers, as well as artists, throughout the ages. The exhibition unveils how spiritual dimensions have been incorporated into artworks since antiquity. Tradition attributes the first icons to Saint Luke who, after Pentecost, is said to have painted three representations of the Virgin Mary. From the first icons of Europe and the Middle East to modern and contemporary works, these pictorial representations of the divine have inspired many believers and artists. The exhibition Icons, curated by Henri Loyrette, former Director of the Musée d'Orsay and Chairman and Director of the Louvre Museum, reveals how spiritual dimensions have been integrated into works of art from Antiquity to the present day. The exhibition shows a selection of ancient icons from Europe and Russia - depicting variously Christ, the Mother of God, or individual saints - the striking simplicity of which sets them apart as timeless objects of veneration. A second set of works by 19th and 20th century artists such as Charles Filiger and Lucien Levy-Dhurmer explores the frontal and depth-less composition of icons. The exhibition also discusses the use that contemporary artists like Yan Pei-Ming and Wim Delvoye make of iconographic language. Exhibition: Boghossian Fondation, Villa Empain, Brussels, Belgium (06.05-14.11.2021)
Frontispizseite: Catalogue publié à l'occasion de l'exposition "Icons", Fondation Boghossian, Villa Empain, Bruxelles, 6 mai - 24 octobre 2021
Keywords: Ikone; Ausstellungskatalog -- Fondation Boghossian -- 06.05.2021-24.10.2021 -- Brüssel